Histori Hadits Karya Imam Muslim: Peran Penting Kitab Hadits Shahih Muslim dalam Mendefinisikan Pendidikan - Ma'sum, Muhammad Asrori (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
This article describes some aspects of the Book of Shahih Muslim. Oneof the main elements of the Book is the personal and intellectualintegrity of the authors that secured the hadiths collected. The hadithswere collected in line with restricted requirement, both thetransmintters and the texts. The Book was composed thoroughly andsystematically. In addition, the Book also deals with education as inhadiths no. 4656 and 836 in which the latter explains aboutprohibition to talk while praying, and an educator. The word Ù…ÙØ¹Ù’Ù„ÙÙŠÙ’Ù…Ù‹Ø§ inthis hadiths means educator.